Associations of microbiota and toll-like receptor signaling pathway in esophageal adenocarcinoma. Issue 1 (December 2016) - Zaidi, Ali; Kelly, Lori; Kreft, Rachael; Barlek, Mark; Omstead, Ashten; Matsui, Daisuke; Boyd, Natalie; Gazarik, Kathryn; Heit, Megan; Nistico, Laura; Kasi, Pashtoon; Spirk, Tracy; et al.
Abstract Background Toll-like receptors (TLRs) recognize known molecules from microbes and have an established role in tumorigenesis. Using a rat model of esophageal adenocarcinoma, and human clinical samples, we investigated genes central to TLR-mediated signal transduction and characterized the esophageal microbiome across the spectrum of esophageal adenocarcinoma carcinogenesis. Methods We surgically induced bile/acid reflux in rats and their esophagi were harvested at 40 weeks post-surgery. Tissue samples from the model were selected for gene expression profiling. Additionally, for rat and human samples microbiome analysis was performed using PCR-ESI-MS-TOF technology with validation by fluorescence in situ hybridization. Results Gene expression results in the rat model indicated a significant upregulation of TLRs 1-3, 6, 7 and 9 in EAC compared to normal epithelium. PCR-ESI-MS-TOF analysis revealed a prevalence of Escherichia coli in Barrett's esophagus (60 %) and esophageal adenocarcinoma (100 %), which was validated by fluorescence in situ hybridization. In the human clinical samples, Streptococcus pneumonia was detected in high abundance in gastroesophageal reflux disease and Barrett's esophagus (50–70 %) in comparison to tumor adjacent normal epithelium, dysplasia, and esophageal adenocarcinoma (20–30 %).E. coli was detected in the Barrett's esophagus and esophageal adenocarcinoma groups but was absent in the tumor adjacent normal epithelium, dysplasia, and the gastroesophageal reflux disease groups. Conclusions We demonstrated an association between the TLR signaling pathway andE. coli hinting towards possible early molecular changes being mediated by microbes in the rat model of esophageal adenocarcinoma carcinogenesis. Studies on human clinical samples also corroborate results to some extent; however, a study with larger sample size is needed to further explore this association.